Medical Education Amidst the COVID-19 Pandemic: A Takeaway from Perspectives of Medical Students of Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background: The objective of this study was to understand the factors which have positively and negatively affected delivery of medical education in Bangladesh during the COVID-19 epidemic and to apply this knowledge to improve preparedness in the event of future COVID spikes or other pandemics.Materials and methods: A 20-question survey was constructed and responses from over 300 medical students across Bangladesh were received and statistically examined by chi-squared, logistic regression and latent class analysis.Results: Quality of internet connection has the biggest impact on delivery of highquality online courses. General experience with online course delivery through number of courses attended and year in the program were also impactful. Latent class analysis indicated that two classes of students existed with regards to their answers (Yes/No/Undecided) as to whether they would attend class or sit professional exams if schools reopened. The characteristics of each class were diverse and enabled a glimpse into the psyche of the students.Conclusions: The results demonstrated a need for government to ensure every one has access to a good quality internet. Not only will it improve the perception of online medical courses, it will prevent students from unnecessary travelling increasing the risk of transmission. With experience in developing online curricula, the misconception that it is inferior to classroom equivalent may be reduced. More confidence in the quality of online classes may encourage more students that are apprehensive about the professional exams to regain their self-confidence and sit them and increase the pool of independently practicing physicians in Bangladesh.Chatt Maa Shi Hosp Med Coll J; Vol.21 (1); January 2022; Page 41-46